Making the Connection: Researcher and Organizational Facilitators and Barriers to Meaningful Engagement with Policymakers - Yussuf-Homenauth, Sabella; Ferreira-Legere, Laura; Paterson, J Michael; Hayes, Anne (International Journal of Population Data Science, 2026)
Bridging the gap between research and policy is crucial to creating evidence-based policies that improve health and social outcomes. As a health data steward holding administrative health data in Ontario, Canada, existing relationships between health data researchers and policymakers were well established at ICES but often lacked transparency and broader visibility. To understand these relationships in practice, we mapped the engagement process, including its policy implications and identified researcher and organizational attributes that fostered meaningful engagement. Using an environmental scan and key informant interviews, we explored how ICES engages with policymakers at the project, program, and organizational levels. Eight case studies were identified, and interviews were conducted with project leads to understand the nature of the engagements and discuss challenges and opportunities to improve engagement. The project identified two primary pathways for policy engagement, 10 core themes, and several researcher and organizational facilitators and barriers. Key themes that emerged included the importance of fostering relationships early, the need for a flexible research program structure to respond to dynamic policy needs, and the reciprocal value of partnership with patient advocacy groups and community organizations. We will leverage our project findings to develop capacity-building resources for researchers wishing to engage policymakers more effectively. This project highlights key areas for researchers and organizations to strengthen policy engagement in research. Understanding how relationships among researchers, research organizations, and policymakers are established and sustained is essential to strengthening evidence-to-policy engagement.